S inorhizobium fredii HH 103 bacteroids are not terminally differentiated and show altered O ‐antigen in nodules of the Inverted Repeat‐Lacking Clade legume G lycyrrhiza uralensis - Juan C. Crespo‐Rivas; Ibtissem Guefrachi; Kenny C. Mok; José A. Villaécija‐Aguilar; Sebastián Acosta‐Jurado; Olivier Pierre; José E. Ruiz‐Sainz; Michiko E. Taga; Peter Mergaert; José M. Vinardell (Environmental Microbiology, 2016)
Summary In rhizobial species that nodulate inverted repeat‐lacking clade ( IRLC ) legumes, such as the interaction between S inorhizobium meliloti and M edicago , bacteroid differentiation is driven by an endoreduplication event that is induced by host nodule‐specific cysteine rich ( NCR ) antimicrobial peptides and requires the participation of the bacterial protein BacA . We have studied bacteroid differentiation of S inorhizobium fredii HH 103 in three host plants: G lycine max , C ajanus cajan and the IRLC legume G lycyrrhiza uralensis . Flow cytometry, microscopy analyses and viability studies of bacteroids as well as confocal microscopy studies carried out in nodules showed that S . fredii HH103 bacteroids, regardless of the host plant, had deoxyribonucleic acid (DNA) contents, cellular sizes and survival rates similar to those of free‐living bacteria. Contrary to S . meliloti , S . fredii HH 103 showed little or no sensitivity to M edicago NCR 247 and NCR 335 peptides. Inactivation of S . fredii HH 103 bac A neither affected symbiosis with G lycyrrhiza nor increased bacterial sensitivity to M edicago NCRs . Finally, HH 103 bacteroids isolated from G lycyrrhiza , but not those isolated from C ajanus or G lycine , showed an altered lipopolysaccharide. Our studies indicate that , in contrast to the S . meliloti ‐ M edicago model symbiosis, bacteroids in the S . fredii HH 103‐ G lycyrrhiza symbiosis do not undergo NCR ‐induced and bac A ‐dependent terminal differentiation.

Sinorhizobium fredii HH103 does not strictly require KPS and/or EPS to nodulate Glycyrrhiza uralensis, an indeterminate nodule-forming legume - Isabel Margaret-Oliver; Wang Lei; Maribel Parada; Miguel A. Rodríguez-Carvajal; Juan C. Crespo-Rivas; Ángeles Hidalgo; Antonio Gil-Serrano; Javier Moreno; Dulce N. Rodríguez-Navarro; Ana Buendía-Clavería; Javier Ollero; José E. Ruiz-Sainz; et al. (Archives of Microbiology, 2012)